Biological indicators to check water quality in plastic-heavy water bodies - Rudkiwal, Anukul (Journal of Ecobiotechnology, 2022)
Water quality is a canonical group of physical, chemical, and biological properties of the given water. The environment and its compartments have been severely polluted by heavy metals and plastic waste. This has compromised the ability of the environment to foster life and render its intrinsic values. Human population increase and consistent demand for heavy metals and plastic products are responsible for the continuous increase in the production of plastic and heavy waste and its accompanied environmental pollution. Biological indicators help in indicating and monitoring the health of the environment. Here, an overview of recent achievements in checking water quality and water pollution trends has been summarized. Papers that reported environmental and public health effects related to plastic-heavy pollutants have also been reviewed. The research for this article intends to further facilitate the R&D initiatives of Jozbiz Technologies Pvt. Ltd.